2009
DOI: 10.1179/136217109x441191
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of creep-weak zones (white bands) in grade 91 weld metal

Abstract: A microstructural study of creep failure in grade 91 weld metal has revealed two primary modes of creep failure. In addition to creep fractures along columnar grain boundaries (typical of weld metal creep failure), creep fractures were also found along creep-weak 'white bands' which had formed at the inter-bead boundaries. The white-band regions consisted of material where the M 23 C 6 carbides had dissolved during creep testing; the loss of carbides had allowed recrystallisation of the martensitic structure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Such precipitate free zones have been observed before in 9Cr weld metal [4] and it was shown in that work that the PFZ developed during creep testing of the weld metal due to carbon diffusion down activity gradients associated with local variations in the weld metal composition. These variations were quantified, with the main variation being in chromium level, where the PFZs were observed to have chromium levels typically 1.5 wt% less than those of the surrounding material, causing the carbon to diffuse down the activity gradient to the high chromium material.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Such precipitate free zones have been observed before in 9Cr weld metal [4] and it was shown in that work that the PFZ developed during creep testing of the weld metal due to carbon diffusion down activity gradients associated with local variations in the weld metal composition. These variations were quantified, with the main variation being in chromium level, where the PFZs were observed to have chromium levels typically 1.5 wt% less than those of the surrounding material, causing the carbon to diffuse down the activity gradient to the high chromium material.…”
Section: Discussionsupporting
confidence: 72%
“…However, creep failures within this type of weld metal have also been reported, typically with cracking occurring along the coarse columnar grain boundaries [4]. Therefore, selection of a consumable that provides a strong weld metal can be significant in increasing the service life of a welded pipe.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [8], Zhang et al [9] and Allen et al [10] reported creep damage occurring within P91 and P92 weld metals. Among other things, so-called white bands, which were formed between the individual welding layers, have been identified as the cause of damage.…”
Section: Introductionmentioning
confidence: 99%
“…The total damage was caused by the combination of the individual crack phenomena. Zhang et al [9] also described the "white bands" with regard to creep strength as a detrimental factor, since they cause Type I cracks in the columnar weld metal areas to grow together and accelerate the damage, in particular under a load transverse to the weld seam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation